Community assembly, coexistence and the environmental filtering metaphor - Kraft, Nathan J. B.; Adler, Peter B.; Godoy, Oscar; James, Emily C.; Fuller, Steve; Levine, Jonathan M. (Functional ecology, 2015)
Summary One of the most pervasive concepts in the study of community assembly is the metaphor of the environmental filter, which refers to abiotic factors that prevent the establishment or persistence of species in a particular location. The metaphor has its origins in the study of community change during succession and in plant community dynamics, although it has gained considerable attention recently as part of a surge of interest in functional trait and phylogenetic‐based approaches to the study of communities. While the filtering metaphor has clear utility in some circumstances, it has been challenging to reconcile the environmental filtering concept with recent developments in ecological theory related to species coexistence. These advances suggest that the evidence used in many studies to assess environmental filtering is insufficient to distinguish filtering from the outcome of biotic interactions. We re‐examine the environmental filtering metaphor from the perspective of coexistence theory. In an effort to move the discussion forward, we present a simple framework for considering the role of the environment in shaping community membership, review the literature to document the evidence typically used in environmental filtering studies and highlight research challenges to address in coming years. The current usage of the environmental filtering term in empirical studies likely overstates the role abiotic tolerances play in shaping community structure. We recommend that the term ‘environmental filtering’ only be used to refer to cases where the abiotic environment prevents establishment or persistence in the absence of biotic interactions, although only 15% of the studies in our review presented such evidence. Finally, we urge community ecologists to consider additional mechanisms aside from environmental filtering by which the abiotic environment can shape community pattern. Lay Summary